PATRONAGE OF HIV/AIDS VOLUNTARY COUNSELLING AND TESTING (VCT) AMONG UNIVERSITY STUDENTS IN GHANA - Tenkorang, Sylvester; Boe-Doe, Kennedy; Adu, Joseph (African Journal of Education and Practice, 2022)
Purpose: This study investigated the factors influencing patronage of HIV/AIDS Voluntary Counselling and Testing (VCT) among students in the University of Cape Coast. Methodology: Descriptive survey research design was adopted for the study. Referring from Krejcie and Morgan's (1970) Sample Determination Table, a sample of 376 students was chosen using convenience sampling from a population of 18949 students. Data were collected using questionnaire adapted from the instrument of Kabiri (2016) administered online. Data were analysed using means and standard deviations. Findings: The study revealed that the students had high level of knowledge about HIV/AIDS VCT and its importance but had low level of knowledge about VCT centres. The study found that the respondents were willing to go to HIV/AIDS VCT Centre to check their HIV/AIDS status and knew of some friends who had gone for HIV/AIDS VCT. However, it was clear that the respondents themselves had not visited VCT centres. Additionally, it was shown in this study by the respondents that willingness, perception of risk associated with their sexual lives, positive perception about VCT, attitude of service provides and ease of access to VCT centres are factors which would influence them to patronize HIV/AIDS VCT. Unique Contribution to Theory, Practice and Policy: Theoretically, the study has highlighted that having awareness of VCT and its importance was not enough to make students patronize VCT services. This means that knowledge and awareness alone was not enough to influence patronage of services.It can also be said that the theory of planned behaviour reviewed in the study was confirmed because a lot of elements are involved in people deciding to engage in specific behaviours. To improve the patronage of VCT, efforts should be put into making VCT centers easily accessible to students. Policy makers are alerted on the low patronage of HIV/AIDS VCT among university students so they can streamline their policies to aid in increasing patronage of VCT by university students.